Analysis of Psychological Influences on Navigation Use While Driving Based on Extended Theory of Planned Behavior. Issue 9 (September 2019) - Yao, Xianglin; Wu, Yiping; Liu, Hao; Zhao, Xiaohua; Bian, Yang; Qu, Weina
As GPS navigation systems become more powerful, they offer the convenience of more efficient travel, and the use of such navigational aids while driving is now prevalent. Numerous issues still exist during actual use, however, such as incomprehensibility and inaccuracy of voice navigation prompts. The majority of studies have focused on humanized design and the influence on driving behavior of GPS navigation systems, while the psychological factors underlying drivers' decisions to use them have received little attention. This study employs the extended theory of planned behavior (TPB) to investigate the psychological factors that influence drivers' use of GPS navigation systems, including the additional variables of navigation involvement, navigation information quality, and distraction perception. Independent t -tests revealed that female, non-professional, novice, and highly educated drivers were more likely to use navigation systems. Factors analysis proved the extended TPB questionnaire to be valid and reliable. Structural equation modeling showed that attitude (0.19), subjective norms (0.14), perceived behavioral control (0.29), navigation involvement (0.36), and information quality (0.16) significantly influenced drivers' intentions on the use of navigation. However, distraction perception (–0.05) had no significant influence. These findings demonstrate the need for navigation systems which serve drivers better. For navigation system manufacturers, the humanized design should be strengthened. For highway transportation agencies, more consistent designs for road signs are needed to improve the cooperativity between navigation and traffic signs.